2016
DOI: 10.1097/01.prs.0000475781.60962.f0
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Computed Tomographic Evaluation of Alveolar Bone Formation in Patients with Unilateral Cleft Lip and Palate after Early Secondary Gingivoalveoloplasty

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 50 publications
0
7
0
9
Order By: Relevance
“…The osteogenesis phenomenon after orthodontic treatment is described in the literature. Meazzini et al found that early secondary gingivoalveoloplasty promotes adequate bone growth in the alveolar and nasal regions [24]. The rate of permanent tooth eruption remains normal [18].…”
Section: Discussionmentioning
confidence: 99%
“…The osteogenesis phenomenon after orthodontic treatment is described in the literature. Meazzini et al found that early secondary gingivoalveoloplasty promotes adequate bone growth in the alveolar and nasal regions [24]. The rate of permanent tooth eruption remains normal [18].…”
Section: Discussionmentioning
confidence: 99%
“…[3437] We combined the evaluation of panoramic radiographs with analysis of CT images in order to assess the bone remodeling of postoperational mandible as thorough as possible. [38,39] Third, bone remodeling controlled by mechanical loading may also account for such discrepancy. For those patients receiving BSSRO surgery, they usually possess a balanced mechanical loading and masticatory function of the mandible after surgery, which is different with the experimental animals in which the nerve transection may lead to disuse of unilateral mandible.…”
Section: Discussionmentioning
confidence: 99%
“…95,96,99,166 Σημαντικές προσπάθειες έχουν γίνει για την αξιολόγηση της τρισδιάστατης μορφολογίας της οστικής γέφυρας. [167][168][169]…”
Section: ακτινογραφικες κλιμακες αξιολογησης της επιτυχιας συγκλεισης γναθοσχιστιαςunclassified
“…Οι έρευνες που αξιολογούν τις διαστάσεις, και όχι απλά τον όγκο, της οστικής γέφυρας, στην πλειοψηφία τους δημοσιεύθηκαν τα τελευταία 5 έτη. [166][167][168][169][170]191,[194][195][196][200][201][202][203][204][205][206][207][208] Οι περισσότερες και οι πιο πρόσφατες προτιμούν τη CBCT, έναντι της κλασσικής υπολογιστικής τομογραφίας. 167,191,[194][195][196]201,202,[204][205][206][207][208] Στις εν λόγω δημοσιεύσεις, μετά τη λήψη ή την ανασύνθεση της εικόνας, οι εγκάρσιες τομές διαφοροποιούνται και μπορεί να είναι παράλληλες στο μασητικό επίπεδο, στο επίπεδο της Φρανκφούρτης ή στο επίπεδο της υπερώας ή ακόμη κάθετες στον επιμήκη άξονα του κυνόδοντα όπως φαίνεται στον Πίνακα 13.…”
Section: αξιολόγηση των διαστάσεων της οστικής γέφυραςunclassified
See 1 more Smart Citation